ショウワキチ シュウヘン ノ キョクチフウ - 遊馬, 芳雄; アスマ, ヨシオ; 小松, 麻美; コマツ, アサミ; Asuma, Yoshio; Komatsu, Asami (2010)
P(論文) 昭和基地での局地風であるカタバ風について,地上観測データと高層データをもとに調べた.まず,守田(1968)のカタバ風出現の目安に従い,1999年1月から2003年12月までの5年間の昭和基地地上観測データを用いて,カタバ風と考えられる強風を抽出した.この抽出された強風をカタバ風と見なし,高層データを使ってカタバ風出現時の特徴を調べた.カタバ風は年間を通して検出され,守田(1968)でも指摘されているが,日変化し風速も比較的小さい夏季のカタバ風と,日変化はせず風速や規模も大きい冬季のカタバ風があることが分かった.さらに,アメリカ国立環境予測センター全球客観解析データ(NCEP-FNL)を用いて,カタバ風出現時の総観場や風の水平分布について調べた.夏季のカタバ風は日変化し比較的循環のスケールが小さいのに対し,冬季のカタバ風は総観場とも連携した寒気や循環構造となっていて,循環のスケールも大きいことが分かった.そして,極域のメソスケール気象現象に適応できるように改良されたPolar MM5メソスケール気象モデルを用いて,カタバ風発生時の上層や周囲の環境場の構造および時間変化を調べた. To investigate local winds near Syowa Station, katabatic winds were analyzed for 5 years between January 1999 and December 2003 following Morita's definition (1968) using synoptic hourly observation data at Syowa Station. Appearance frequencies and vertical wind and temperature structures were also examined. It was found that spatially and temporally small scale katabatic winds are predominant in summer and low level strong winds are characteristic in winter. Winter katabatic winds are connected to the large scale atmospheric circulation. These conditions were analyzed and simulated with an objectively analyzed data set (NCEP-FNL) and a meso-scale weather model (Polar MM5). departmental bulletin paper